Molecular epidemiology, risk factors, and outcomes of carbapenem-resistant Klebsiella pneumoniae infection in a tertiary hospital in eastern China: for a retrospective study conducted over 4 years - Cheng, Jun; Zhao, Dongmei; Ma, Xuejiao; Li, Jiabin (Frontiers in Microbiology, 2023)
Objectives: Carbapenem-resistant Klebsiella pneumoniae (CRKP) have undergone extensive dissemination in worldwide resulting in increased mortality. We performed a retrospective analysis of epidemiology and risk factors for the outcome of CRKP infection in a general teaching hospital in China.A molecular and clinical study were conducted for 98 CRKP in a tertiary hospital from January 2013 to December 2016. Carbapenemase gene detection, pulsed-field gel electrophoresis (PFGE) and multilocus sequence typing (MLST) were performed. Logistic regression was also used to identify the risk factors associating with the 30-day mortality.The producition of KPC cabapenemase was the main resistant mechanism and increased annually with a significant difference. However, the molecular outcome revealed the dominance and diversity in CRKP with 24 sequence types (STs) and 59 PFGE types (PTs ).The ST11 CRKP were documented as the predominant strains in our study, which showed a significant increasing trend year by year. Additionally, the predominant ST11 CRKP corresponding to PT10 and PT15 remained a typical fashion. Of note, the new advantage PT09 or PT16 were just discovered in 2016 which also corresponding to ST11. Meanwhile, the factors on 30-day mortality and ST11 proportionality with CRKP infection were assessed, which showed that ST11, appropriate empirical treatment, and hospital stays were independently associated with 30-day mortality.Conclusions: ST11 CRKP payed a dominant role in the process, but the homology of these strains was polymorphic and the advantage clusters would be changed by evolution.Additionally, besides appropriate empirical treatment and hospital stays, ST11 CRKP was independently associated with the 30-day mortality, first reported as we know.